2021
DOI: 10.1016/j.ygyno.2020.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Genetically predicted circulating protein biomarkers and ovarian cancer risk

Abstract: Most women with epithelial ovarian cancer (EOC) are diagnosed after the disease has metastasized and survival in this group remains poor. Circulating proteins associated with the risk of developing EOC have the potential to serve as biomarkers for early detection and diagnosis. We integrated largescale genomic and proteomic data to identify novel plasma proteins associated with EOC risk. MethodsWe used the germline genetic variants most strongly associated (P<1.5×10 −11 ) with plasma levels of 1,329 proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
(34 reference statements)
1
23
0
Order By: Relevance
“…12 In addition, Considine et al confirmed the overlapping genetic association signals between plasma protein levels of MFAP2 and EOC risk by using the regional genome map. 13 Based on this, we evaluated MFAP2 expression using the TCGA database of ovarian cancer cohort high-throughput RNA-sequencing data Gene Expression Profiling Interactive Analysis (GEPIA; http://gepia.cancer-pku.cn).…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, Considine et al confirmed the overlapping genetic association signals between plasma protein levels of MFAP2 and EOC risk by using the regional genome map. 13 Based on this, we evaluated MFAP2 expression using the TCGA database of ovarian cancer cohort high-throughput RNA-sequencing data Gene Expression Profiling Interactive Analysis (GEPIA; http://gepia.cancer-pku.cn).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the gene that codes MFAP2 is located at 1p36.13, and is associated with several malignant tumor types ( 6 , 7 ). Consequently, MFAP2 is upregulated in breast cancer ( 8 ), thyroid cancer ( 9 ), melanoma ( 10 ), ovarian cancer ( 11 ) and gastric cancer ( 12 , 13 ), and associated with the occurrence and progression of these tumors. Previous studies have also shown that MFAP2 is upregulated in HCC ( 14 ), but its role in the occurrence and development of the disease is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is also the constitutive protein of most vertebrate microfibrils [ 25 ]. A representative feature of MFAP2 is its capacity to work with TGF- β family growth factors, Notch, and Notch ligands, as well as a variety of elastins [ 26 ]. Mutations of MFAP2 gene may indicate thrombosis, thoracic aneurysms, metabolic diseases, and osteopenia in humans [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study pointed out that MFAP2 is a novel microRNA-29 target, and miR-29/MFAP2/integrin α 5 β 1/FAK/ERK1/2 might be an important carcinogenic pathway in gastric cancer progression [ 10 ]. Another study has also indicated the relevance of MFAP2 in hepatic carcinoma, whereby MFAP2 overexpression in hepatic carcinoma is associated with cancer staging, poor OS, and disease-specific survival [ 9 , 26 ]. An in vitro experiment showed that downregulation of MFAP2 inhibited the proliferation and migration levels of liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%